2017
DOI: 10.4103/ijo.ijo_365_16
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of macular pigment optical density in patients with dry and wet age-related macular degeneration

Abstract: Aim:The aim of the study was to evaluate the macular pigment optical density (MPOD) levels in patients with wet age-related macular degeneration (AMD), dry AMD, and also in healthy controls.Settings and Design:This study was conducted at Department of Ophthalmology, and the study design was a prospective study.Patients and Methods:Forty-eight patients with wet AMD, 51 patients with dry AMD, and 50 controls were included in the study. All patients were naive to both previous lutein or zeaxanthin administration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 32 publications
1
4
0
Order By: Relevance
“…We did not find significant relationships between MPOD and age in our patients, a finding that is in agreement with the previous studies,[13] although a small age-dependent decline has also been reported. [1920]…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…We did not find significant relationships between MPOD and age in our patients, a finding that is in agreement with the previous studies,[13] although a small age-dependent decline has also been reported. [1920]…”
Section: Discussionsupporting
confidence: 94%
“…Since the MP is entirely of dietary origin, supplementation with lutein, zeaxanthin, and meso-zeaxanthin may reduce the risk of macular degeneration. [613] A positive association was noted between MPOD levels, central foveal thickness and higher intake of foods containing carotenoids. [12] Akuffo et al .…”
Section: Discussionmentioning
confidence: 99%
“…The macula benefits from the ability of MPs to quench reactive oxygen species generated photochemically, metabolically, and arriving as toxins from poor diet or other insults such as smoking [2,10]. Low levels of MPs have therefore been implicated in long-term accumulation of photochemical damage [12] and with increased likelihood of developing age-related macular degeneration (AMD) [13][14][15][16][17][18][19]. A method of assessing macular pigment density (MPD) that is suitable for mass screening could provide a valuable tool for informing people of their natural levels of protection so that they can be empowered to take preventative actions to further protect their eyes from violet/blue light and reduce other risk factors including smoking [20,21] and obesity [22,23].…”
Section: Introductionmentioning
confidence: 99%
“…On the contrary, Westrup et al ( 35 ) reported a negative correlation between the juxtafoveal MPOD and retinal thickness. According to present knowledge, the impact of MPOD over retina thickness has still remained controversial ( 32 - 38 ).…”
Section: Discussionmentioning
confidence: 99%
“…Greater MPOD may protect retinal neurons against dairy stress and improve connections between retinal neurons. Recently, the relationship between age-related macular degeneration and MPs has mostly been studied ( 14 , 38 - 41 ). However, there is no study investigating the density of MPs in amblyopic eyes.…”
Section: Discussionmentioning
confidence: 99%